2011
DOI: 10.1007/s00395-011-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Coronary arterioles in type 2 diabetic (db/db) mice undergo a distinct pattern of remodeling associated with decreased vessel stiffness

Abstract: Background Little is known about the impact of type 2 diabetes mellitus (DM) on coronary arteriole remodeling. The aim of this study was to determine the mechanisms that underlie coronary arteriole structural remodeling in type 2 diabetic (db/db) mice. Methods and Results Passive structural properties of septal coronary arterioles isolated from 12- and 16-wk-old diabetic db/db and control mice were assessed by pressure myography. Coronary arterioles from 12-wk-old db/db mice were structurally similar to age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
78
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 56 publications
24
78
2
Order By: Relevance
“…19 A previous study has shown that inward hypertrophic remodeling of coronary arterioles isolated from diabetic mice is associated with a decrease in vascular wall stiffness and reduced MBF and CFR. 20 In this study, our findings were consistent with the current literature and showed that FTY720 treatment lowered the expression of TGF-β and collagen, and reduced the extent of myocardial interstitial fibrosis in diabetic rat heart tissues.…”
Section: Discussionsupporting
confidence: 92%
“…19 A previous study has shown that inward hypertrophic remodeling of coronary arterioles isolated from diabetic mice is associated with a decrease in vascular wall stiffness and reduced MBF and CFR. 20 In this study, our findings were consistent with the current literature and showed that FTY720 treatment lowered the expression of TGF-β and collagen, and reduced the extent of myocardial interstitial fibrosis in diabetic rat heart tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Our recent work suggests that coronary microvascular remodeling in type 2 diabetic db/db mice differed from aortic and mesenteric resistance vessels 1,12 . To understand molecular mechanisms that account for these differences, in vitro studies using low passage VSMCs are necessary.…”
Section: Representative Resultsmentioning
confidence: 92%
“…However, we have demonstrated vascular-bed specific remodeling in coronary, aortic, and mesenteric circulations of db/db mice 1 , suggesting the VSMCs in each vascular bed may be different. Therefore, it is necessary to isolate VSMCs from each vascular bed in order to better understand the pathological changes occurring in each set of VSMCs.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations